The Yearbook Photo and Graduation Speech: Intersections of Sexual Identity, Gender Identity, Gender Expression, and Race. (March 2016) - Fleig, Jeffrey
Only 48.6% of University Council For Educational Administration (UCEA) institutions which focus on social justice in principal preparation programs address sexual orientation, this case describes how the completion of an equity audit for an educational leadership course compelled Principal Olson to reflect on his identity as a social justice leader. The racial identity development of Principal Olson led him to understand his own Whiteness and privilege and how his actions not only marginalized students of color but also students who are lesbian, gay, bisexual, transgender, or questioning (LGBTQ). The day before graduation, Principal Olson listened as the class president rehearsed her speech where she told the audience she is transgender. This is not a debate of whether the speech should be given, but the issue is how Principal Olson will respond when questioned.